Pelatihan Pedoman Umum Ejaan Bahasa Indonesia dalam Penulisan Spanduk dan Baliho di Percetakan Roza 6 Suku Kota Solok - Halid, Elan; Putri, Mega; Wirasty. B, Rini; Rahayu, Zona Rida; Marta, Redo Andi (ASOSIASI IDEBAHASA KEPRI, 2025)
The Indonesian Language Spelling Guide (Pedoman Umum Ejaan Bahasa Indonesia, or PUEBI) is the official guideline for correct spelling in the Indonesian language. A banner is a medium used to convey specific information aimed at the general public. A billboard is a promotional medium used to announce events or activities related to the broader community. Printing plays a crucial role in ensuring that banners and billboards are free from spelling or grammatical errors. If spelling is incorrect, such errors can create a negative perception of both the client and the printing company, potentially damaging the professional image of both parties. This community engagement activity was carried out by providing training to employees of Roza 6 Suku printing company in Solok City. The training used lectures, Q&A, discussions, and practical exercises on punctuation in title writing on banners and billboards. Overall, participants were receptive to the material presented by the trainer, which offered an alternative solution to improve their knowledge and skills in spelling Indonesian correctly, with a focus on proper punctuation in banner and billboard writing. The application of PUEBI in printing also raises awareness of the importance of language quality in visual communication, demonstrating the social responsibility of the printing company to preserve language integrity.